2011
DOI: 10.1080/1533256x.2011.618067
|View full text |Cite
|
Sign up to set email alerts
|

Hitting Bottom: Help Seeking Among Alcoholics Anonymous Members

Abstract: Alcoholics Anonymous (AA) members' self-reports ( N = 263) of "hitting bottom" and seeking help were analyzed using 1-way analysis of variance and chi-square analyses of 23 dependent variables. AA members self-identified a range of bottoms: high-bottom (36.1%), middle (44.5%), and low (19.4%). Whites were 2.4 times more likely than non-Whites to identify as high-bottoms. Lower bottoms were associated with multidrug use, constant drinking, and alcohol-related problems. High bottoms more likely entered AA via me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Although previous studies found that incarceration reinforced continued involvement in criminal behavior (Burnett & Maruna, 2004; Farrall & Calverley, 2006), we found that incarceration along with various other factors provided several participants a source of motivation toward exit (Horgan, 2009). Much like former alcoholics who experienced “hitting rock bottom” (Greil & Rudy, 1983, p. 8; see also Young, 2011) before deciding to take action toward change, some members of our sample came to see prison as a direct consequence of hate group involvement and solid evidence they had reached their lowest point. Incarceration and other contact with law enforcement may have provided a dramatic illustration that involvement is a “dead end” and thus may be especially powerful in terms of “crystallizing discontent” (Paternoster & Bushway, 2009) and spurring disillusionment.…”
Section: The Process Of Exitmentioning
confidence: 94%
“…Although previous studies found that incarceration reinforced continued involvement in criminal behavior (Burnett & Maruna, 2004; Farrall & Calverley, 2006), we found that incarceration along with various other factors provided several participants a source of motivation toward exit (Horgan, 2009). Much like former alcoholics who experienced “hitting rock bottom” (Greil & Rudy, 1983, p. 8; see also Young, 2011) before deciding to take action toward change, some members of our sample came to see prison as a direct consequence of hate group involvement and solid evidence they had reached their lowest point. Incarceration and other contact with law enforcement may have provided a dramatic illustration that involvement is a “dead end” and thus may be especially powerful in terms of “crystallizing discontent” (Paternoster & Bushway, 2009) and spurring disillusionment.…”
Section: The Process Of Exitmentioning
confidence: 94%
“…In sum, for Paternoster and Bushway, desistance comes about due to the active cognitive agency of desisters thinking about their futures, weighing out costs and benefits of deviance against a future self, and ultimately making a clean break with the past. Three markers of identity change highlighted by Paternoster and Bushway are (a) crystallization of discontent, (b) changes in institutional/social relationships, and (c) a “break from the past” as key markers in redefining self (see also Young, 2011).…”
Section: Identity Theorymentioning
confidence: 99%
“…Effective strategies might parallel those that have been found to be effective to facilitate help seeking by people with addictions-namely, motivational interviewing and arranging contact with people already in 12-step recovery (Timko & DeBenedetti, 2007;Young, 2011). Effective strategies might parallel those that have been found to be effective to facilitate help seeking by people with addictions-namely, motivational interviewing and arranging contact with people already in 12-step recovery (Timko & DeBenedetti, 2007;Young, 2011).…”
Section: Summary Conclusion and Future Directionsmentioning
confidence: 99%